The Mummy shop - Longstaff, Abie. (London : Scholastic Children's Books, 2013)
Does your mummy tell you off for jumping on your bed? Does she make you eat vegetables when you don't want to? Then call The Mummy Shop, and we will help you find the perfect new mummy. 100% satisfaction guaranteed! When a little boy grows tired of his mummy, he calls The Mummy Shop for help. But after a number of mishaps and misunderstandings, he starts to think he may have made a big mistake... A laugh-out-loud tale of one boy's quest to find the perfect mummy... his own!
K-3.
Keywords: Mother -- Fiction